Study of NEP 2020: Issues, Approaches, Challenges, Oppurtunities and Criticism: An analysis of the National Education Policy 2020 and its impact on India's education system (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A well-defined education policy and the future is important for the country at school and collegelevels because of the fact that education leads to economic and social development. Different countriesuse different education systems with due regard to culture and traditions and take different stages duringtheir life cycle at school and college education levels to make it work. The National Education Policy2020 (NEP 2020), approved by the Indian Union Cabinet on July 29, 2020, sets out the vision for India'snew education system. The new policy replaces the previous National Education Policy, 1986. Thispolicy is a comprehensive framework for primary education towards higher education and vocationaltraining in rural and urban areas of India. This policy aims to transform India's education system by 2021.Shortly after the policy was released, the government made it clear that no one would be forced to learnany particular language and that the method of teaching would not be diverted from English to anyregional language. The language policy in the NEP is a schools to decide on the application.Education inIndia is a study of the Related List.Policy 2020. A national education policy should be applied to allschools in India by 2022.